Identifying predictors of student satisfaction and student motivation in the framework of assuring quality in the delivery of higher education services - Stukalina, Yulia (Business, Management and Economics Engineering, 2014)
Nowadays, the quality of educational services provided by a university is a crucial aspect of the education managers’ strategy in the customer-driven education context, quality assurance in education being an essential issue to be promoted in European higher education institutions. Students’ evaluation of the educational services (that is consumer-oriented assessment) can be regarded as one of the most significant educational management tools used for stimulating quality enhancement in a university. It is vital for supporting decision-making process. A special emphasis may be put on monitoring student satisfaction with the educational services and student motivation toward studies. Understanding the central factors that are supposed to influence and predict student satisfaction and student motivation may provide education managers with best possible solutions to improve quality of the educational services in a higher education institution. This paper presents the results of an empirical study performed in Riga Technical University. The study was aimed at identifying the basic determinants (predictors) of student satisfaction and motivation in the framework of the ESP (English for Specific Purposes) course.